Kaygusuz Abdalova Kaz Şathiyesi : An Attempt of Mythological Analysis (Prilozi za orijentalnu filologiju, 2017)
The paper deals with the analysis of a new variant of the poem Kaz Şathiyesi by Kaygusuz Abdal. The author compares various variants of the above-mentioned poem. They are the three variants from Turkey and two from Bulgaria (Aşik Hasaıı varyaııti, Gölpiııarli varyaııti, H. Küçük varyanti, A. Güzel varyanti, H. ibram varyanti). The paper also deals with the astrological symbolism of some of the words used in these variants (goose, nightingale, cauldron, ete.). In the elosing seetion of the paper the author brings up some novelties in the interpretation of the said poem.